Are we ready for Roundup Ready TM foods? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Against the Grain, The Genetic Transformation of Global Agriculture. M Lappe and B Bailey. Earthscan Publications Ltd, 1998. 176 pp.